Adsorption Power of Activated Charcoal from Coconut Shells on Lead Metal (Pb) in Well Water - Mardjan Paputungan; Nita Suleman; Yulia Rahman Yunus (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine the results of the characterization and ability of activated charcoal (activated with KOH) to absorb lead metal (Pb). The procedure used is the process of carbonizing coconut shells in an airtight container at a temperature of 300ºC. Activation of coconut shell charcoal was carried out by immersing the charcoal powder in a KOH solution with variations of 1 M, 3 M, and 5 M. Characterization of activated charcoal powder was carried out on pore morphology using SEM-EDX, and XRD to identify the crystal phase, and AAS to determine the concentration lead metal (Pb). Based on the research results, the morphology of the charcoal before activation had a lot of impurities and the pores tended to be closed. After activation, the impurities disappeared and the pores were open. The crystal phase before and after activation was identified as 23.40% and 14.3% (calculated to be low), with the specific peak at 2θ, namely the corner area of 10º-80º. The adsorption capacity and efficiency obtained on activated charcoal with a KOH concentration of 1 M was 0.00194 mg/g and 23.66%, on activated charcoal the concentration of 3 M KOH was 0.00407 mg/g and 49.61%, the concentration of activated charcoal KOH 5 M is 0.00757 mg/g and 92.36%. Thus, the greater the KOH concentration, the greater the adsorption capacity and efficiency.